Urban Spatial Structure and the Density of Retail Shops in Cities. - Samburu, Peter Maluki (Scientific & Academic Publishing, 2023)
The variability of the location and retail shop density relative to the urban structure of informal and formal settlements are pervasive issues in many cities. Therefore, this study examines the relationship between street metric properties and retail shop density and the association between spatial intelligibility, synergy and retail shop density. The study was based on the space syntax theory and focused on selected planned and unplanned settlements in the city of Kisumu in Kenya. Data was collected through inventory surveys and analysed through spatial kernel density analytic estimation, axial line analysis and regression analysis. The retail density of the four neighbourhoods was around 50% in Manyatta, 24.4% in Migosi, 16.6% in Arina and 8.9% in Nyalenda. Results indicated a significant association between street metric properties and retail density in the study (Arina: F=3.41, p=0.012; Migosi: F=34.13, p=0.000; Manyatta: F=9.918, p=0.000; and Nyalenda: F=13.837, p=0.000), rejecting the null hypothesis at 0.05 significance level. Findings on synergy indicated a stronger relationship between local integration (R3) and global integration (Rn) in Manyatta (R2 =0.6777) but not in Nyalenda (R2 =0.4949), Migosi (R2 =0.4881) and Arina (R2 =0.3461). Intelligibility results showed relatively low scores in each settlement indicating poor navigability of the settlements. However, the informal settlements of Manyatta and Nyalenda showed better intelligibility (R2 =0.3752 and R2 =0.2496) than the formal settlements (Migosi and Arina), which showed R 2 =0.1380 and R2 =0.1744, respectively. The study findings indicate that street metric properties vary across settlements and have different impacts on retail shop density, with informal settlements exhibiting stronger synergies compared to formal neighbourhoods. Additionally, all settlements lack intelligibility, suggesting that the street networks are not well connected, both locally and citywide. To address this issue, the study recommends improving citywide accessibility and ensuring interconnected streets to enhance settlement intelligibility.
Keywords: Urban Structure.; Retail Density.; Street Metrics.; Intelligibility.; Synergy.; Space Syntax Theory.